Creating a New Structure for Research on Health Care Effectiveness. (1st March 2005) - Kupersmith, Joel; Sung, Nancy; Genel, Myron; Slavkin, Harold; Califf, Robert; Bonow, Robert; Sherwood, Louis; Reame, Nancy; Catanese, Veronica; Baase, Catherine; Feussner, John; Dobs, Adrian; et al.
Abstract : Effectiveness research (a term we use in preference to the more confining and difficult health services or outcomes research ) evaluates the clinical setting and the health care system on which it depends. It uses a variety of health care assessment techniques and the practical clinical trial to inform clinical practice, quality interventions, and health policy decisions. Effectiveness research had not had sufficient public or private funding to produce the information needed to facilitate evidence-based health care improvement. However, recent trends, such as the likelihood for continued substantial increases in health care costs and concern regarding the quality and safety of the US health care system, are among the important arguments for increasing its funding and capacity. We propose a new entity, a public-private consortium to expand and offer new capability and resources in this area. The consortium would consist of all relevant public and private entities. It would be organized into an executive committee, which would identify research priorities and panels to design requests for proposals. Competitive peer-reviewed proposals, transparency and balance of forces in choice of topics, conduct of research, and interpretation of results would be important features. Metrics for success would be use of the data derived from consortium projects in medical decision making and benefit design. The consortium would provide balance and potential mediation of conflicting or competing interests in which all stakeholders will be present to establish the rules. Broad representation of all interests would serve to avoid the economic, policy, and political issues that have bedeviled past efforts. Models for the consortium include the Health Effectiveness Institute, the Centers for Education and Research on Therapeutics, and the Transportation Research Board.